(NkLIMATI^ESKIJ REVIM aRKTIKI NA RUBEVE (BXX (NI (BXXI (NWW(B. /s - (NaLEKSEEW(B, (Ng(B.(Nw(B.s; (NpODGORNYJ(B, (Ni(B.(Na(B.s; (NsWQ]ENNIKOW(B, (Np(B.(Nn(B.s; (NkRUTSKIH(B, (NbORIS aNDREEWI^s; (NaRKTI^ESKIJ I aNTARKTI^ESKIJ NAU^NO(B-(NISSLEDOWATELXSKIJ INSTITUTs ((NsANKT(B-(NpETERBURG (B:s (NgIDROMETEOIZDAT(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 189-196 (166 (NNAZW(B.)s
Keywords: (NkLIMAT s -- (NaRKTIKAs